2013
DOI: 10.1111/ctr.12304
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative left ventricular hypertrophy is associated with reduced patient survival after liver transplantation

Abstract: LVH is frequently diagnosed in patients on the waiting list and influences survival after LT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Since, cardiac dysfunction in cirrhosis seems not to be associated with the severity of liver disease [27], both an accurate patient selection for liver transplant [28,29] and a precise investigation for cirrhotic cardiomyopathy are mandatory. Indeed, cirrhotic cardiomyopathy may influence the outcome after liver transplantation [30][31][32]; moreover, liver transplantation may be responsible for additional intra-and postoperative short-and long-term cardiac morbidity [33].…”
Section: Pre-transplant Investigative Methodsmentioning
confidence: 99%
“…Since, cardiac dysfunction in cirrhosis seems not to be associated with the severity of liver disease [27], both an accurate patient selection for liver transplant [28,29] and a precise investigation for cirrhotic cardiomyopathy are mandatory. Indeed, cirrhotic cardiomyopathy may influence the outcome after liver transplantation [30][31][32]; moreover, liver transplantation may be responsible for additional intra-and postoperative short-and long-term cardiac morbidity [33].…”
Section: Pre-transplant Investigative Methodsmentioning
confidence: 99%
“…6 Also some studies have found an association between DD and post-OLT mortality while others have found no association. 4,[7][8][9] However, most of these investigations have defined DD based on only one or two echocardiographic parameters, likely adding error to estimation of DD. For instance, e/a is load-dependent parameter, and thus by itself a poor indicator of the grade of DD.…”
Section: Introductionmentioning
confidence: 99%
“…(5) The presence of diastolic dysfunction could be involved in hepatorenal syndrome (HRS) and in the morbidity of some of the major procedures, such as surgery, TIPS, and liver transplantation. (6)(7)(8) However, because diagnostic criteria for CCMP are not usually used in routine, its prevalence in this population and the incidence of post-TIPS cardiac decompensation are not well known. A better evaluation of the risk of post-TIPS cardiac decompensation should improve the patient's selection and help to prevent congestive heart failure.…”
mentioning
confidence: 99%